2014
DOI: 10.1371/journal.pone.0109169
|View full text |Cite
|
Sign up to set email alerts
|

LIN28B Promotes Colon Cancer Migration and Recurrence

Abstract: LIN28B is involved in “stemness” and tumourigenesis by negatively regulating the maturation of let-7 microRNA family members. In this study, we showed that LIN28B expression promotes migration and recurrence of colon cancer. Immunohistochemistry and reverse-transcription polymerase chain reactions were performed to detect LIN28B expression in colon cancer tissue microarrays, paraffin-embedded surgical resected tissues and cancer cells. Loss-of-function, migration and proliferation analyses were performed to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 25 publications
2
33
0
Order By: Relevance
“…Furthermore, we analyzed the largest cohort of human CRC samples to date and observed that LIN28A and/or LIN28B expression correlated with invasive tumor pathology and poor prognosis, phenotypes accurately reflected in our murine model. While prior murine models have used LIN28B exclusively (King et al 2011a,b;Madison et al 2013;Pang et al 2014), we demonstrated an equally potent role of LIN28A in tumorigenesis and progression in both our murine model and human CRC. Our models illuminate several novel aspects of LIN28-induced tumor biology.…”
Section: Discussionmentioning
confidence: 40%
“…Furthermore, we analyzed the largest cohort of human CRC samples to date and observed that LIN28A and/or LIN28B expression correlated with invasive tumor pathology and poor prognosis, phenotypes accurately reflected in our murine model. While prior murine models have used LIN28B exclusively (King et al 2011a,b;Madison et al 2013;Pang et al 2014), we demonstrated an equally potent role of LIN28A in tumorigenesis and progression in both our murine model and human CRC. Our models illuminate several novel aspects of LIN28-induced tumor biology.…”
Section: Discussionmentioning
confidence: 40%
“…For instance, several studies showed that Lin28B is overexpressed in colon cancer and promotes colon cancer progression [8, 9], whereas the expression and functions of Lin28A in colon cancer are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this variant was also found to be associated with the risk and survival of cancer, such as epithelial ovarian cancer [32], colon cancer [33,34], non-small cell lung cancer [35], oral cavity cancer [36], and neuroblastoma [16]. LIN28B protein was found to be unregulated in colon tumours, and the overexpression correlated with reduced patient survival and increased probability of tumour recurrence [34,37]; besides, LIN28B can promote migration, invasion, and malignant transformation of cells [38]. Furthermore, studies also found that the overexpression of LIN28B was associated with poor prognosis in head and neck cancer [39], oral squamous cell carcinoma patients [40,41], gastric cancer [42], breast cancer [43], ovarian cancer [44], and neuroblastoma [16,45,46].…”
Section: Discussionmentioning
confidence: 99%